PERANAN USAHA KECIL (PEDAGANG KAKI LIMA) DALAM MENINGKATKAN PENDIDIKAN ANAK DI DESA PEMENANG BARAT KECAMATAN PEMENANG KABUPATEN LOMBOK UTARA - Syaiful Amri; Umar Said (Valid: Jurnal Ilmiah, 2016)
The aim of this research was to determine the condition of small businesses,children’s education level, and the role of small businesses (vendors) in improvingchildren's education in the village of West Pemenang North Lombok District. Thisresearch was conducted by using a qualitative approach (qualitative descriptive), whereresearcher was the key instrument of the research and data source was performed with purposive sampling. The methods of collecting data used in this research were interview, observation, and documentation. Data analysis technique was inductive, by reducing the data, displaying data and drawing conclusions. Validity of the data was performed by the extension of the participation, perseverance observation, triangulation, inspection through discussion and the adequacy of reference. According to the results of the research conducted by the researcher; the condition of small businesses provided a very important role on the improvement of children's education, especially in the financing needs of the school. The level of education of children in the village of Pemenang has increased from 2010 to 2011. For kindergarten amounted to 10 people, Primary School/Islamic Elementary amounted to 311 people, Junior high school / MTs amounted to 37 people, High School / Madrasah Aliyah amounted to 219 people, and for Higher Education numbered 30 people. The role of small businesses (vendors) in improving the education of children in the village of West Pemenang has a very important role in improving children's education, especially in finance continuity of education, facilities and infrastructure or equipment children's education